Preparation method of metal single-atom carbon-based composite material and metal single-atom carbon-based composite material
Patent Information
- Application Number
- CN202510560704.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-04-30
AI Technical Summary
但其不足之处在于,受限于传统的基于经验的材料选择与设计,材料的均匀性较差,很难均匀的改善每个以M-SA为极化中心的固有极化损耗
[0025]与现有技术相比,本发明利用新颖的曲率调制策略对单原子碳材料进行功能设计,通过改变载体球壳的直径,均匀的调制了载体表面电场,有效的提升了材料电磁响应能力,进而提高电磁波吸收性能。本发明首次将模板法和点击策略相结合制备了曲率可调的单原子材料将并引入到磁波吸收领域,所述曲率可调的单原子材料具有优异的电磁波吸收性能。本发明具有以下优点:
Smart Images

Figure CN120222039B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterials, specifically relating to a method for preparing and applying a single-atom carbon-based composite material. Background Technology
[0002] With the rapid development of electronic communication technology and intelligent detection equipment, while modernization has significantly improved social productivity and quality of life, it has also given rise to increasingly serious electromagnetic environmental pollution problems. High-frequency electromagnetic radiation not only easily leads to measurement errors in precision instruments and distortion of information transmission, but may also have irreversible effects on human physiological functions through long-term cumulative effects.
[0003] Metal single-atom (M-SA) based materials, possessing maximum atomic utilization, well-defined single-atom dispersion, and unique coordination environments, exhibit physical properties significantly different from corresponding clusters, nanoparticles, and bulk materials, showing great promise for applications across various fields. Among these, metal single-atom materials anchored on nano-carbon exhibit limitless potential in EMW absorbing materials and intelligent electromagnetic functional devices due to their tunable conductivity and strong polarization relaxation. Existing atomic-level absorbing materials utilize strategies such as introducing defects, doping with heteroatoms, or constructing heterojunctions (Y. Shi, Z. Ma, X. Zhang, F. Yan, Y. Zhao, C. Zhu, Y. Chen, Adv. Funct. Mater. 2024, 34, 2313483) to modulate the electronic structure of single-atom materials, enhancing their dielectric and magnetic loss capabilities. However, their drawback lies in the poor uniformity of the materials due to limitations imposed by traditional experience-based material selection and design, making it difficult to uniformly improve the inherent polarization loss of each M-SA-centered polarization center.
[0004] Material surfaces with sharp curvature allow for highly concentrated electric fields, a phenomenon known as the classic lightning rod effect, which has been widely used in surface plasmon resonance (SPR) sensing, nanomicroscopy, and antenna design. Currently, research is exploring the application of curvature modulation in the design of electromagnetic wave absorbing materials. For example, the strain on the Fe-N bonds induced by highly curved Turing surfaces effectively breaks the symmetric distribution of charge around Fe atoms (Z.Ma, Y.Shen, X.Zhang, B.Li, Y.Chen, C.Zhu, Adv. Funct. Mater. 2025, 35, 2413784), significantly increasing the dielectric loss of the material. Yao et al. proposed the nano-curvature field effect of space-inverted symmetry-broken structures and the surface electric field enhancement effect of multi-shell structures, amplifying the polarization of the conjugate-non-conjugate interface (J.Tao, K.Zou, J.Zhou, H.Wu, L.Xu, J.Wang, X.Tao, H.Huang, Z.Yao, Nat Commun 2024, 15, 10337), thus improving electromagnetic wave absorption performance. These works demonstrate that curvature engineering can effectively improve electromagnetic wave absorption performance. The invention patent with application number 202510132062.6 provides a single-atom modified carbon composite microwave absorbing material and its preparation method. The single-atom microwave absorbing material is prepared by click confinement strategy and has excellent electromagnetic microwave absorption performance. Its shortcoming is that it does not involve the material curvature control mechanism. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention proposes a method for preparing and applying a metal single-atom carbon-based composite material. The technical solution is as follows: A method for preparing a metal single-atom carbon-based composite material involves using a template method to coat an organic polymer monomer onto the surface of a template agent to prepare a spherical shell with a diameter of 50 nm to 1000 nm. The hard template is then removed by etching with an etchant to obtain a hollow polymer spherical shell with a diameter of 50 nm to 1000 nm. Subsequently, a metal salt is mixed uniformly with the hollow spherical shell and subjected to pyrolysis to obtain the final product. The metal salt is a transition metal salt from the 4th to 6th period.
[0006] Preferably, the diameter is 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm, and the template agent is polystyrene, polymethyl methacrylate or silica microspheres.
[0007] Preferably, the metal in the metal salt is Ni, Cu, Co, Mn, Fe, Zn, Mo, V, Ag, Ir, Rh, or Pt.
[0008] Preferably, the organic polymer monomers selected are pyrrole, thiophene, dopamine, vinylpyrrolidone, and aniline.
[0009] Preferably, the preparation method includes the following steps:
[0010] S1, the monomer solution of the polymer is added to the template agent dispersion to coat the polymer on the surface of the template agent. After the reaction is completed, the OP@TP-X complex is obtained, where X is the diameter, OP is an organic polymer, TP is the template agent, and the template agent is polystyrene, polymethyl methacrylate or silica microspheres.
[0011] S2, the prepared OP@TP-X composite is dispersed in an etchant for etching, and after the reaction is completed, a hollow polymer spherical shell OP-X composite is obtained;
[0012] S3, uniformly disperse the transition metal salts of periods 4 to 6 in an ethanol solution;
[0013] S4. The hollow spherical shell is added to the metal salt solution, and the mixture is stirred at room temperature to react evenly, thus obtaining the complex.
[0014] S5. The composite is placed in a tube furnace and carbonized at 600~900℃ in an argon atmosphere to obtain a metal single-atom carbon composite material M / NC-X, where M is a metal.
[0015] Preferred,
[0016] S1, the weight ratio of template agent to water is 1:10000~1:500, the weight ratio of organic polymer monomer to template agent is 5:1~1:5, and the organic polymer monomer is dispersed in ethanol at a concentration of 0.05~0.2g / ml;
[0017] S2, the ratio of OP@TP-X complex to etchant is such that each gram of OP@TP-X complex is dispersed in 200~500ml of etching solution, and the stirring time of S2 is 24~72h;
[0018] S4, the weight ratio of metal salt to hollow spherical shell is 1:100~1:5, and the reaction time of S4 is 2~4h;
[0019] S5, with a heating rate of 5~10℃ / min.
[0020] The organic polymer monomers are coated onto the surface of the template agent by means of a template method, under the action of hydrochloric acid as a co-solvent and ammonium persulfate as an oxidant. The concentration of hydrochloric acid is 37%, and the amount used is 40~100ml. The concentration of ammonium persulfate solution is 0.02~0.1g / ml, and the amount used is 20~50ml.
[0021] The present invention also provides a single-atom carbon-based composite material prepared according to the preparation method described above, and applies it to electromagnetic wave absorption and shielding.
[0022] Preferably, the single-atom carbon-based composite material is mixed with polyvinyl butyral at a mass ratio of 1:4 to 1:7 and then dispersed in an ethanol solution. After uniform mixing, an M / HNC-X microwave absorbing film is obtained.
[0023] Preferably, the molecular weight of the polyvinyl butyral is 170,000 to 200,000; and the mass concentration of the polyvinyl butyral relative to the polyvinyl butyral-ethanol system is 0.3 wt% to 0.6 wt%.
[0024] Beneficial effects
[0025] Compared with existing technologies, this invention utilizes a novel curvature modulation strategy to functionally design single-atom carbon materials. By changing the diameter of the carrier spherical shell, the electric field on the carrier surface is uniformly modulated, effectively enhancing the material's electromagnetic response capability and thus improving its electromagnetic wave absorption performance. This invention is the first to combine the template method and the click strategy to prepare curvature-tunable single-atom materials and introduce them into the field of magnetic wave absorption. These curvature-tunable single-atom materials exhibit excellent electromagnetic wave absorption performance. This invention has the following advantages:
[0026] (1) The preparation method of the present invention is simple to operate, safe and controllable, and has low energy consumption. The obtained single-atom material with adjustable curvature has a uniform diameter distribution, and the induced electric field on its surface caused by the nano curvature is uniformly modulated.
[0027] (2) The single-atom material with adjustable curvature obtained by the present invention has low density and is a strong candidate for lightweight absorbing material. In addition, the hollow structure is conducive to multiple scattering of electromagnetic waves, and the material can dissipate electromagnetic waves more effectively.
[0028] (3) The advantage of the curvature modulation process in this invention is that the increase in the electromagnetic wave absorption intensity of the sample originates from the amplification effect of the nano-curvature field on the surface electric field. This effect promotes the transfer of electrons from metal single atoms (M-Sa) to local carbon (C) and nitrogen (N) atoms by enhancing the carrier separation efficiency and charge migration dynamics, thereby exacerbating the local charge imbalance. This significant change in charge distribution leads to the synergistic enhancement of local dipole moment and polarizability, optimizing the inherent polarization loss characteristics of each dipole with M-Sa as the polarization center, and ultimately achieving efficient dissipation and absorption of electromagnetic waves.
[0029] (4) This invention employs an ingenious material design method to rationally construct a single loss mechanism model, and deeply analyzes its potential loss mechanism through system experiments and theoretical calculations. In addition, the curvature-tunable single-atom material prepared by this invention can be used as an absorbing film. Among them, Ni / HNC-200 has an effective absorption bandwidth of up to 5.24 GHz when the matching thickness is 1.97 mm, and the reflection loss can reach -74.1 dB when the matching thickness is 2.84 mm, which has good electromagnetic absorption performance.
[0030] (5) The single-atom material with adjustable curvature obtained by the present invention can be directly sprayed onto the surface of the device to be processed using a spray gun, and can perform electromagnetic wave absorption and shielding treatment on the device to be processed in multiple scenarios. Attached Figure Description
[0031] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, and the advantages of the present invention in the above and other aspects will become clearer.
[0032] Figure 1 Transmission electron microscope (TEM) images of the materials prepared in Examples 1-4.
[0033] Figure 2 The image shows an electron microscope image with spherical aberration correction of the material prepared in Example 2.
[0034] Figure 3 The X-ray diffraction patterns are of the materials prepared in Examples 1-4.
[0035] Figure 4 Inductively coupled mass spectrometry (ICMMS) of the materials prepared in Examples 1-4.
[0036] Figure 5 The graph shows the conductivity test results of the materials prepared in Examples 1-4.
[0037] Figure 6 The graph shows the test results of conduction loss and polarization loss of the materials prepared in Examples 1-4.
[0038] Figure 7 The image shows the microwave absorption performance of the material prepared in Example 1.
[0039] Figure 8 The image shows the microwave absorption performance of the material prepared in Example 2.
[0040] Figure 9 The image shows the microwave absorption performance of the material prepared in Example 3.
[0041] Figure 10 The image shows the microwave absorption performance of the material prepared in Example 4.
[0042] Figure 11 The diagram shows the microwave absorption performance of the materials obtained in Examples 5-8.
[0043] Figure 12 The diagram shows the microwave absorption performance of the materials obtained in Examples 9-11.
[0044] Figure 13 The diagram shows the microwave absorption performance of the materials obtained in Examples 12-14.
[0045] Figure 14 This is a schematic diagram showing the resin board before (left) and after (right) spraying in Test Example 3.
[0046] Figure 15 This is a test diagram showing the microwave absorption performance of the thin film layer of the microwave-absorbing coating sprayed onto the resin board in Example 3. Detailed Implementation
[0047] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.
[0048] Example 1
[0049] Step 1: Add 20 mL of 50 nm polystyrene microsphere aqueous dispersion (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion);
[0050] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0051] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-50.
[0052] Step 4: Immerse the HPPy@Ps-50 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-50;
[0053] Step 5: Dissolve 200 mg of nickel porphyrin (NiPor) and 68 µL of thionyl chloride (SOCl2) in 15 mL of LDMF, sonicate for 10 minutes to convert the carboxyl group to an acyl chloride group, and then add 115 mg of catalyst 4-dimethylaminopyridine (DMAP) to form a raw material solution.
[0054] Step 6: Dissolve 346 µL of triethylamine in 30 mL of LDM, then uniformly disperse 200 mg of the HPPy-50 microspheres prepared in Step 4 in the solution, and sonicate for 45 minutes to form a homogeneous suspension. Then, add the raw material solution obtained in Step 5 dropwise to the suspension, and stir at 80 °C for 48 hours. After the reaction, wash and dry the product, then dry it under an argon atmosphere at a heating rate of 5 °C / min, and finally carbonize it at 700 °C from room temperature to obtain the product Ni / HNC-50.
[0055] Example 2
[0056] Step 1: Add 20 mL of a polystyrene microsphere aqueous dispersion with a particle size of 200 nm (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion);
[0057] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0058] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-200.
[0059] Step 4: Immerse the HPPy@Ps-200 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-200;
[0060] Step 5: Dissolve 200 mg of nickel porphyrin (NiPor) and 68 µL of thionyl chloride (SOCl2) in 15 mL of LDMF, sonicate for 10 minutes to convert the carboxyl group to an acyl chloride group, and then add 115 mg of catalyst 4-dimethylaminopyridine (DMAP) to form a raw material solution.
[0061] Step 6: Dissolve 346 µL of triethylamine in 30 mL of LDM, then uniformly disperse 200 mg of the HPPy-200 microspheres prepared in Step 4 in the solution, and sonicate for 45 minutes to form a homogeneous suspension. Then, add the raw material solution obtained in Step 5 dropwise to the suspension, and stir at 80 °C for 48 hours. After the reaction, wash and dry the product, then heat it in an argon atmosphere at a heating rate of 5 °C / min for carbonization treatment from room temperature to 700 °C to obtain the product Ni / HNC-200.
[0062] Example 3
[0063] Step 1: Add 20 mL of a 500 nm polystyrene microsphere aqueous dispersion (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion).
[0064] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0065] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-500.
[0066] Step 4: Immerse the HPPy@Ps-500 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-500;
[0067] Step 5: Dissolve 200 mg of nickel porphyrin (NiPor) and 68 µL of thionyl chloride (SOCl2) in 15 mL of LDMF, sonicate for 10 minutes to convert the carboxyl group to an acyl chloride group, and then add 115 mg of catalyst 4-dimethylaminopyridine (DMAP) to form a raw material solution.
[0068] Step 6: Dissolve 346 µL of triethylamine in 30 mL of LDM, then uniformly disperse 200 mg of the HPPy-500 microspheres prepared in Step 4 in the solution, and sonicate for 45 minutes to form a homogeneous suspension. Then, add the raw material solution obtained in Step 5 dropwise to the suspension, and stir at 80 °C for 48 hours. After the reaction, wash and dry the product, then heat it in an argon atmosphere at a heating rate of 5 °C / min for carbonization treatment from room temperature to 700 °C to obtain the product Ni / HNC-500.
[0069] Example 4
[0070] Step 1: Add 20 mL of a 1000 nm polystyrene microsphere aqueous dispersion (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion).
[0071] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0072] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-1000.
[0073] Step 4: Immerse the HPPy@Ps-1000 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-1000;
[0074] Step 5: Dissolve 200 mg of nickel porphyrin (NiPor) and 68 µL of thionyl chloride (SOCl2) in 15 mL of LMF, and sonicate for 10 minutes to convert the carboxyl groups to acyl chloride groups. Then add 115 mg of catalyst 4-dimethylaminopyridine (DMAP) to form a raw material solution. Step 6: Dissolve 346 µL of triethylamine in 30 mL of LMF, and then uniformly disperse 200 mg of HPPy-1000 microspheres prepared in Step 4 in the solution. Sonicate for 45 minutes to form a uniform suspension. Then add the raw material solution prepared in Step 5 dropwise to the suspension and stir at 80 °C for 48 hours. After the reaction, wash and dry the product, and then heat it in an argon atmosphere at a heating rate of 5 °C / min to carbonize it from room temperature to 700 °C to obtain the product Ni / HNC-1000.
[0075] Example 5
[0076] Step 1: Add 20 mL of 50 nm polystyrene microsphere aqueous dispersion (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion);
[0077] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0078] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-50.
[0079] Step 4: Immerse the HPPy@Ps-50 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-50; Step 5: Place the product obtained in Step 4 in an argon atmosphere and dry it at a heating rate of 5℃ / min. The product is then heated from room temperature to 700℃ for carbonization treatment to obtain the product, labeled HNC-50.
[0080] Example 6
[0081] Step 1: Add 20 mL of a polystyrene microsphere aqueous dispersion with a particle size of 200 nm (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion);
[0082] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0083] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-200.
[0084] Step 4: Immerse the HPPy@Ps-200 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-200; Step 5: Place the product obtained in Step 4 in an argon atmosphere and dry it at a heating rate of 5℃ / min. The product is then heated from room temperature to 700℃ for carbonization treatment to obtain the product, labeled HNC-200.
[0085] Example 7
[0086] Step 1: Add 20 mL of a 500 nm polystyrene microsphere aqueous dispersion (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion).
[0087] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0088] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-500.
[0089] Step 4: Immerse the HPPy@Ps-500 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-500; Step 5: Place the product obtained in Step 4 in an argon atmosphere and dry it at a heating rate of 5℃ / min. Then heat the product from room temperature to 700℃ for carbonization treatment to obtain the product, labeled as HNC-500.
[0090] Example 8
[0091] Step 1: Add 20 mL of a 1000 nm polystyrene microsphere aqueous dispersion (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion).
[0092] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0093] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-1000.
[0094] Step 4: Immerse the HPPy@Ps-1000 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-1000;
[0095] Step 5: Place the product obtained in step 4 in an argon atmosphere and dry it at a heating rate of 5℃ / min. Then, heat the product from room temperature to 700℃ for carbonization treatment to obtain the product, which is labeled as HNC-1000.
[0096] Example 9
[0097] Step 1: Add 20 mL of a polystyrene microsphere aqueous dispersion with a particle size of 200 nm (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion);
[0098] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0099] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-200.
[0100] Step 4: Immerse the HPPy@Ps-200 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-200;
[0101] Step 5: Dissolve 200 mg of copper porphyrin (CuPor) and 68 µL of thionyl chloride (SOCl2) in 15 mL of LDM, and sonicate for 10 minutes to convert the carboxyl groups to acyl chloride groups. Then add 115 mg of catalyst 4-dimethylaminopyridine (DMAP) to form a raw material solution. Step 6: Dissolve 346 µL of triethylamine in 30 mL of LDM, and then uniformly disperse 200 mg of HPPy-200 microspheres prepared in Step 4 in the solution. Sonicate for 45 minutes to form a uniform suspension. Then add the raw material solution prepared in Step 5 dropwise to the suspension and stir at 80 °C for 48 hours. After the reaction, wash and dry the product, and then heat it in an argon atmosphere at a heating rate of 5 °C / min to carbonize it from room temperature to 700 °C to obtain the product Cu / HNC-200.
[0102] Example 10
[0103] Step 1: Add 20 mL of a 500 nm polystyrene microsphere aqueous dispersion (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion).
[0104] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0105] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-500.
[0106] Step 4: Immerse the HPPy@Ps-500 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-500;
[0107] Step 5: Dissolve 200 mg of copper porphyrin (CuPor) and 68 µL of thionyl chloride (SOCl2) in 15 mL of LMF, and sonicate for 10 minutes to convert the carboxyl groups to acyl chloride groups. Then add 115 mg of catalyst 4-dimethylaminopyridine (DMAP) to form a raw material solution. Step 6: Dissolve 346 µL of triethylamine in 30 mL of LMF, and then uniformly disperse 200 mg of HPPy-500 microspheres prepared in Step 4 in the solution. Sonicate for 45 minutes to form a uniform suspension. Then add the raw material solution prepared in Step 5 dropwise to the suspension and stir at 80 °C for 48 hours. After the reaction, wash and dry the product, and then heat it in an argon atmosphere at a heating rate of 5 °C / min to carbonize it from room temperature to 700 °C to obtain the product Cu / HNC-500.
[0108] Example 11
[0109] Step 1: Add 20 mL of a 1000 nm polystyrene microsphere aqueous dispersion (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion).
[0110] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0111] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-1000.
[0112] Step 4: Immerse the HPPy@Ps-1000 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-1000;
[0113] Step 5: Dissolve 200 mg of copper porphyrin (CuPor) and 68 µL of thionyl chloride (SOCl2) in 15 mL of LMF, and sonicate for 10 minutes to convert the carboxyl groups to acyl chloride groups. Then add 115 mg of catalyst 4-dimethylaminopyridine (DMAP) to form a raw material solution. Step 6: Dissolve 346 µL of triethylamine in 30 mL of LMF, and then uniformly disperse 200 mg of HPPy-1000 microspheres prepared in Step 4 in the solution. Sonicate for 45 minutes to form a uniform suspension. Then add the raw material solution prepared in Step 5 dropwise to the suspension and stir at 80 °C for 48 hours. After the reaction, wash and dry the product, and then heat it in an argon atmosphere at a heating rate of 5 °C / min to carbonize it from room temperature to 700 °C to obtain the product Cu / HNC-1000.
[0114] Example 12
[0115] Step 1: Add 20 mL of a polystyrene microsphere aqueous dispersion with a particle size of 200 nm (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion);
[0116] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0117] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-200.
[0118] Step 4: Immerse the HPPy@Ps-200 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-200;
[0119] Step 5: Dissolve 200 mg of cobalt porphyrin (CoPor) and 68 µL of thionyl chloride (SOCl2) in 15 mL of LDM, sonicate for 10 minutes to convert the carboxyl group to an acyl chloride group, and then add 115 mg of catalyst 4-dimethylaminopyridine (DMAP) to form a raw material solution.
[0120] Step 6: Dissolve 346 µL of triethylamine in 30 mL of LDM, then uniformly disperse 200 mg of the HPPy-200 microspheres prepared in Step 4 in the solution, and sonicate for 45 minutes to form a homogeneous suspension. Then, add the raw material solution obtained in Step 5 dropwise to the suspension, and stir at 80 °C for 48 hours. After the reaction, wash and dry the product, then heat it in an argon atmosphere at a rate of 5 °C / min for carbonization treatment from room temperature to 700 °C to obtain the product Co / HNC-200.
[0121] Example 13
[0122] Step 1: Add 20 mL of a 500 nm polystyrene microsphere aqueous dispersion (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion).
[0123] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0124] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-500.
[0125] Step 4: Immerse the HPPy@Ps-500 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-500;
[0126] Step 5: Dissolve 200 mg of cobalt porphyrin (CoPor) and 68 µL of thionyl chloride (SOCl2) in 15 mL of LMF, and sonicate for 10 minutes to convert the carboxyl groups to acyl chloride groups. Then add 115 mg of catalyst 4-dimethylaminopyridine (DMAP) to form a raw material solution. Step 6: Dissolve 346 µL of triethylamine in 30 mL of LMF, and then uniformly disperse 200 mg of HPPy-500 microspheres prepared in Step 4 in the solution. Sonicate for 45 minutes to form a uniform suspension. Then add the raw material solution prepared in Step 5 dropwise to the suspension and stir at 80 °C for 48 hours. After the reaction, wash and dry the product, and then heat it in an argon atmosphere at a heating rate of 5 °C / min to carbonize it from room temperature to 700 °C to obtain the product Co / HNC-500.
[0127] Example 14
[0128] Step 1: Add 20 mL of a 1000 nm polystyrene microsphere aqueous dispersion (mass concentration of 25 mg / mL) to 1000 mL of ultrapure water and ultrasonically disperse for 3 hours to obtain a uniform dispersion system (polystyrene dispersion, hereinafter referred to as PS dispersion).
[0129] Step 2: Dissolve 1 mL of freshly distilled pyrrole monomer in 20 mL of ethanol, and then add it dropwise to the PS dispersion obtained in Step 1 while stirring continuously;
[0130] Step 3: Place the reaction system obtained in Step 2 in an ice bath environment, and add 90 mL of hydrochloric acid (HCl, mass fraction of 37 wt.%) and 20.0 mL of ammonium persulfate aqueous solution (abbreviated as APS, mass concentration of 0.05 mg / mL, as oxidant) in sequence. After reacting for 12 h, wash and dry to obtain the product, named HPPy@Ps-1000.
[0131] Step 4: Immerse the HPPy@Ps-1000 product obtained in Step 3 in 1L of N,N-dimethylformamide (DMF) to remove the polystyrene template and obtain hollow polypyrrole microspheres; then wash with deionized water and freeze-dry to obtain the product, named HPPy-1000;
[0132] Step 5: Dissolve 200 mg of cobalt porphyrin (CoPor) and 68 µL of thionyl chloride (SOCl2) in 15 mL of LDM, sonicate for 10 minutes to convert the carboxyl group to an acyl chloride group, and then add 115 mg of catalyst 4-dimethylaminopyridine (DMAP) to form a raw material solution.
[0133] Step 6: Dissolve 346 µL of triethylamine in 30 mL of LDM, then uniformly disperse 200 mg of HPPy-1000 microspheres obtained in Step 4 in the solution, and sonicate for 45 minutes to form a homogeneous suspension. Then, add the raw material solution obtained in Step 5 dropwise to the suspension, and stir at 80 °C for 48 hours. After the reaction, wash and dry the product, then heat it in an argon atmosphere at a rate of 5 °C / min for carbonization treatment from room temperature to 700 °C to obtain the product Co / HNC-1000.
[0134] Test Example 1
[0135] The physicochemical properties of the materials prepared in Examples 1-4 were tested: Radio electron microscopy (RFM) imaging was performed on the materials prepared in Examples 1-4, and the imaging results are as follows: Figure 1 As shown; Figure 1 The materials prepared in Examples 1-4 are shown to have a uniform hollow spherical shell morphology and no metal nanoparticles were observed.
[0136] Aberration-corrected electron microscope images of the material prepared for Example 2 were obtained. Figure 2 This directly proves that the metal in the Ni / HNC-200 material exists in the form of highly dispersed single-atom sites.
[0137] X-ray diffraction patterns were analyzed on the materials prepared in Examples 1-4, and the results are as follows: Figure 3 As shown; Figure 3 The results showed that only graphite peaks were detected in the materials prepared in Examples 1-4, with no corresponding metal peaks, proving that the metal in the prepared materials exists in the form of highly dispersed single-atom sites; the electromagnetic properties of the materials prepared in Examples 1-4 were measured, and the inductively coupled mass spectrometry results were as follows: Figure 3 As shown; Figure 4 The materials prepared in Examples 1-4 are shown to have a similar Ni metal loading of approximately 0.1 wt%; the electrical conductivity of the samples in paraffin was measured as follows: Figure 5 As shown, Figure 5 The electrical conductivity of the materials prepared in Examples 1-4 in paraffin is shown to be 0.0154, 0.0331, 0.0540, and 0.0721 S / m, respectively.
[0138] Test Example 2
[0139] The electromagnetic parameters of the microwave absorbing coatings prepared in Examples 1-14 were measured using a network analyzer (VNA, N5245A, Agilent, USA).
[0140] The test conditions were as follows: (1) Test frequency band: 2~18GHz; (2) Mass composition of the sample: The mass ratio of Ni / HNC-X (X=50, 200, 500 or 1000) prepared in the example to paraffin wax was 1:9; (3) Sample standardization settings: All samples were pressed into standard annular spaces (f: 3.04 mm, f: inout 7.00 mm) by the same mold to maintain the geometric determination; the thickness of all annular spaces was maintained at 2.5 mm; (4) Test algorithm: The relevant electromagnetic parameters were automatically output by Agilent PNA software according to the Nicolson and Ross and Weir algorithm.
[0141] The test results are as follows: Figure 6 The conduction loss and polarization loss of the materials prepared in Examples 1-4 are shown; from Figure 5 It can be found that the enhanced electromagnetic wave absorption capability of single-atom carbon composite microwave absorbing materials with adjustable curvature mainly comes from enhanced polarization loss rather than conduction loss.
[0142] Figures 7-10 The electromagnetic wave absorption properties of the materials prepared in Examples 1-4 are shown; Figures 7-10 The electromagnetic wave absorption performance of the materials prepared in Examples 1-4 is shown. The minimum reflection loss is -11.9dB, -74.1dB, -31.4dB and -20.4dB respectively, and the maximum effective absorption bandwidth is 2.36, 5.24, 4.48 and 5.4 GHz respectively. The above results demonstrate that the polarization loss can be improved by adjusting the curvature of the material to significantly enhance the electromagnetic wave absorption intensity of the sample.
[0143] Figure 11The electromagnetic wave absorption performance of the blank control group without single-atom loading is shown. The minimum reflection loss of the materials prepared in Examples 5-8 is -8.1 dB, -15.1 dB, -15.5 dB, and -13.1 dB, respectively, and the maximum effective absorption bandwidth is 0, 4.88, 4.12, and 3.56 GHz, respectively. Therefore, it can be seen that the electromagnetic wave absorption performance can be significantly improved by synergistically controlling the curvature parameters of the substrate material through single-atom loading. Furthermore, experimental verification shows that when the substrate material exhibits a high-curvature three-dimensional curved surface structure (e.g., hollow carbon nanospheres with a diameter ≤200 nm), the reflection loss of the material loaded with single-atom nickel (Ni) (Ni / HNC-200) reaches -74.1 dB, representing a performance improvement of over 390% compared to the unloaded single-atom material with the same structure (HNC-200). In particular, the absorption intensity of the material is positively correlated with the curvature of the substrate. When the substrate curvature parameter is below the threshold (such as hollow carbon nanospheres with a diameter of 1000 nm), its local structure tends to be planar. At this time, single-atom loading cannot achieve a performance breakthrough (Ni / HNC-1000 reflection loss -20.4 dB vs HNC-1000 -13.1 dB), which fully demonstrates the key role of curvature control in this technical solution.
[0144] Figure 12 The graph shows the electromagnetic wave absorption performance test results of the materials prepared in Examples 9-11 (samples with different curvatures loaded with Cu single atoms). The minimum reflection loss of the materials prepared in Examples 9-11 is -76.3dB, -31.7dB and -20.4dB respectively, and the maximum effective absorption bandwidth is 5.32, 5.4 and 4.08 GHz respectively. Figure 13 The figures show the microwave absorption performance test results of the materials prepared in Examples 12-14. The minimum reflection losses of the materials prepared in Examples 12-14 are -63.3 dB, -24.0 dB, and -19.3 dB, respectively, and the maximum effective absorption bandwidths are 5.48, 4.36, and 5.12 GHz, respectively. It can be observed that the electromagnetic wave absorption performance of the high curvature samples corresponding to different single atoms is greatly improved. The above results fully demonstrate that the polarization loss can be improved by controlling the curvature of the material to significantly enhance the electromagnetic wave absorption performance of the sample.
[0145] Test Example 3
[0146] Testing the microwave absorbing performance of the microwave absorbing material provided by this invention in the field of microwave absorbing coatings: Preparation of microwave absorbing coating: Take 0.05g of Ni / HNC-200 obtained in Example 2, grind it, and add it to 35g of ethanol solution containing 0.16g of polyvinyl butyral. Stir thoroughly to obtain Ni / HNC-200 microwave absorbing coating; then, under an air compressor, use a spray gun to spray the Ni / HNC-200 microwave absorbing material onto various types of boards (the boards include PMMA organic glass boards, inorganic glass boards, resin boards, and PET). The spraying method is as follows: spray a layer of the microwave absorbing coating onto the surface of the board; control the appropriate liquid output and air volume during the spraying process to make the spray fine; after the first layer is slightly dry, continue to spray multiple layers to control the coating thickness; wait for the volatile ethanol solution to dry within about 10 minutes to finally obtain a homogeneous gray film. Figure 14 These are schematic diagrams showing the resin board before (left) and after (right) spraying.
[0147] Its absorption performance was determined using the method described in Example 1, and the test results are as follows: Figure 15 As shown, by comparison, the coating prepared by Ni / HNC-200 and polyvinyl butyral at a mass ratio of 1:5 has a minimum reflection loss of -44.5dB after spraying and film formation.
Claims
1. A method for preparing a single-atom carbon-based composite material, characterized in that, A template method was used to coat organic polymer monomers onto the surface of a template agent to prepare spherical shells with a diameter of 50 nm to 1000 nm. The hard template was then removed by etching with an etchant to obtain hollow polymer spherical shells with a diameter of 50 nm to 1000 nm. A metalloporphyrin containing a carboxyl group was mixed with SOCl2 and catalyzed by 4-dimethylaminopyridine to form a metalloporphyrin solution. The metal in the carboxyl-containing metalloporphyrin was a transition metal from period 4 to 6. The metalloporphyrin solution was then mixed evenly with the hollow polymer spherical shells and pyrolyzed to obtain the final product.
2. The preparation method according to claim 1, characterized in that... The hollow polymer spherical shell has a diameter of 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm, and the template agent is polystyrene, polymethyl methacrylate or silica microspheres.
3. The preparation method according to claim 1, characterized in that... The metal in the metal porphyrin containing a carboxyl group is Ni, Cu, Co, Mn, Fe, Zn, Mo, V, Ag, Ir, Rh, or Pt.
4. The preparation method according to claim 1, characterized in that... The organic polymer monomers are pyrrole, thiophene, dopamine, vinylpyrrolidone, or aniline.
5. The preparation method according to claim 1, characterized in that, Includes the following steps: S1, add the monomer solution of the organic polymer to the template agent dispersion, and coat the organic polymer monomer on the surface of the template agent under the action of co-solvent hydrochloric acid and oxidant ammonium persulfate. After the reaction is completed, the OP@TP‐X complex is obtained, where X is the diameter, OP is the organic polymer monomer, TP is the template agent, and the template agent is polystyrene, polymethyl methacrylate or silica microspheres. S2, the prepared OP@TP‐X composite is dispersed in an etchant for etching, and after the reaction is completed, a hollow polymer spherical shell OP‐X composite is obtained. S3, dispersing carboxyl-containing metalloporphyrins in SOCl2 solution; S4, the hollow polymer shell OP-X composite was added to the metal porphyrin solution and stirred at room temperature to react evenly to obtain the composite; S5. The composite is placed in a tube furnace and carbonized at 600~900°C in an argon atmosphere to obtain a metal single-atom carbon-based composite material.
6. The preparation method according to claim 5, characterized in that... S1, the weight ratio of template agent to water is 1:10000~1:500, the weight ratio of organic polymer monomer to template agent is 5:1~1:5, the organic polymer monomer is dispersed in ethanol at a concentration of 0.05~0.2g / ml, and the reaction time of S1 is 12~24h; S2, the ratio of OP@TP-X complex to etchant is such that each gram of OP@TP-X complex is dispersed in 200~500ml of etching solution, and the stirring time of S2 is 24~72h; S4, the weight ratio of metal salt to hollow spherical shell is 1:100~1:5, and the reaction time of S4 is 2~4h; S5, the heating rate is 5~10°C / min.
7. The preparation method according to claim 5, characterized in that... The organic polymer monomers are coated onto the surface of the template agent by means of a template method, under the action of hydrochloric acid as a co-solvent and ammonium persulfate as an oxidant. The concentration of hydrochloric acid is 37%, and the amount used is 40~100ml. The concentration of ammonium persulfate solution is 0.02~0.1g / ml, and the amount used is 20~50ml.
8. A metal single-atom carbon-based composite material obtained by the preparation method of any one of claims 1-7, used for electromagnetic wave absorption and shielding.
9. The metal single-atom carbon-based composite material according to claim 8, characterized in that... The metal single-atom carbon-based composite material is mixed with polyvinyl butyral at a mass ratio of 1:4 to 1:7 and then dispersed in an ethanol solution. After uniform mixing, an M / HNC-X microwave absorbing film is obtained.
10. The metal single-atom carbon-based composite material according to claim 9, characterized in that... The polyvinyl butyral has a molecular weight of 170,000 to 200,000; the mass concentration of the polyvinyl butyral relative to the polyvinyl butyral-ethanol system is 0.3 wt% to 0.6 wt%.
Citation Information
Patent Citations
Monoatom modified carbon composite wave-absorbing material and preparation method thereof
CN119570444A
Magnetic metal nanoparticle-modified carbon hollow sphere wave-absorbing material and preparation method thereof
CN113597247A